Multifaceted role of geminivirus associated betasatellite in pathogenesis. (18th June 2019) - Gnanasekaran, Prabu; KishoreKumar, Reddy; Bhattacharyya, Dhriti; Vinoth Kumar, R.; Chakraborty, Supriya
Summary: Begomoviruses have emerged as a group of plant pathogens that cause devastating diseases in a wide range of crops in tropical and subtropical regions of the world. Betasatellites, the circular single‐stranded DNA molecules with the size of almost half of that of the associated helper begomoviruses, are often essential for the production of typical disease symptoms in several virus‐host systems. Association of betasatellites with begomoviruses results in more severe symptoms in the plants and affects the yield of numerous crops leading to huge agroeconomic losses. βC1, the only protein encoded by betasatellites, plays a multifaceted role in the successful establishment of infection. This protein counteracts the innate defence mechanisms of the host, like RNA silencing, ubiquitin‐proteasome system and defence responsive hormones. In the last two decades, the molecular aspect of betasatellite pathogenesis has attracted much attention from the researchers worldwide, and reports have shown that βC1 protein aggravates the helper begomovirus disease complex by modulating specific host factors. This review discusses the molecular aspects of the pathogenesis of betasatellites, including various βC1‐host factor interactions and their effects on the suppression of defence responses of the plants.